There's a diplodocus in the house poems - Anonuevo, Rebecca, T.; Bumatay, Sergio (Makati City The Bookmark, Inc., 2016)
"Dinosaurs are timeless charms for everyone. These poems by Rebecca T. Añonuevo explore the secrets to children's minds, beyond their favorite dinosaurs. Sergio Añonuevo III's illustrations transpose the poems to an enchanted plane. Imagination is never as wondrous, as in this book that shows the feast of possibility in the power of language and visual art combined.
Keywords: Children's poetry, Philippine (English).; Philippine poetry (English).